Evaluation of the brachial artery endothelial function in chronic alcohol consumption among males by high‐frequency ultrasonography. Issue 2 (29th December 2016) - Luo, Runlan; Shen, Jiaqi; Zhou, Qiao; Liu, Yue; Li, Guangsen
Abstract : Objective: There is evidence suggesting that different volumes of chronic alcohol consumption have different effects on the endothelium. Therefore, using high‐frequency ultrasonography, we evaluate the effects of the different volume and duration of alcohol intake on brachial artery endothelial function in chronic drinkers. Methods: Ninety‐two male chronic episodic alcoholics were grouped by alcohol intake amount and duration: mild (group B, n=30); ≤90 mg ethanol daily, 3–5 days/wk for 5–8 years; moderate (group C, n=30); 90–150 mg ethanol daily, 3–5 days/wk for 9–20 years; and severe (group D, n=32); ≥150 mg ethanol daily, 6–7 days/wk for more than 10 years. Thirty male nondrinkers were recruited as the control group A. High‐frequency ultrasonography was used to measure brachial artery diameter during rest, during reactive hyperemia and following the administration of nitroglycerin. Endothelial‐dependent brachial artery flow‐mediated dilatation (FMD) and endothelial‐independent brachial artery nitrate‐mediated dilatation (NMD) were calculated. Results: Flow‐mediated dilatation values for group C and D were significantly lower than those for group A and B ( V C =7.63±0.22, V D =5.85±0.23 vs V A =13.35±0.35, V B =12.81±0.36, P <.01). The FMD of group D was significantly lower than that of group C ( P <.01). Meanwhile, the NMD of group D was significantly lower than that of the other groups ( V D =17.33±6.21 vs V A =25.35±7.42, V B =24.52±8.30, V C =23.35±7.27, P <.01). Conclusions: Chronic moderate‐to‐heavy alcohol consumption caused endothelial dysfunction, even damaging vascular smooth muscle cells in cases of heavy alcohol consumption, while abstinence and chronic mild alcoholics caused no effect on endothelial function.